2012
DOI: 10.3389/fnagi.2012.00005
|View full text |Cite
|
Sign up to set email alerts
|

Unfolded protein stress in the endoplasmic reticulum and mitochondria: a role in neurodegeneration

Abstract: Protein-folding occurs in several intracellular locations including the endoplasmic reticulum and mitochondria. In normal conditions there is a balance between the levels of unfolded proteins and protein folding machinery. Disruption of homeostasis and an accumulation of unfolded proteins trigger stress responses, or unfolded protein responses (UPR), in these organelles. These pathways signal to increase the folding capacity, inhibit protein import or expression, increase protein degradation, and potentially t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 136 publications
(179 reference statements)
2
52
0
Order By: Relevance
“…This results in activation of NRF1 and other cytoprotective responses to overcome the mitochondrial stress. Additionally, disruptions in unfolded protein responses in both ER and mitochondria have been implicated in the development of neurodegenerative diseases such as Parkinson's and Alzheimer's diseases among others [56, 57]. …”
Section: Additional Mechanisms Of Mitochondrial Retrograde/stress mentioning
confidence: 99%
“…This results in activation of NRF1 and other cytoprotective responses to overcome the mitochondrial stress. Additionally, disruptions in unfolded protein responses in both ER and mitochondria have been implicated in the development of neurodegenerative diseases such as Parkinson's and Alzheimer's diseases among others [56, 57]. …”
Section: Additional Mechanisms Of Mitochondrial Retrograde/stress mentioning
confidence: 99%
“…This transcription factor displayed a strong effect on the ratio of ADAM10‐ to BACE‐1‐promoter activity in our screening approach, and UPR has already been correlated to neurodegenerative disease in recently rising numbers of publications (reviewed in ref. 16). We investigated the underlying mechanism of ADAM10 regulation by XBP‐1 in cell culture and demonstrate the consistency of our findings by quantitative analysis of mRNA from 2 AD mouse models and cortical tissue of AD postmortem samples.…”
mentioning
confidence: 99%
“…Bcl-2 family can play important roles in prolonged ER stressinduced apoptosis [5,10,30]. In our previous reports [19,22], we showed that the mRNA level of Bcl-2, an anti-apoptotic gene, was drastically increased in DGCN5.…”
Section: Involvement Of Bcl-2 In Drastic Resistance Against Thapsigarmentioning
confidence: 97%
“…Alzheimer's disease, amyotrophic lateral sclerosis and Parkinson's disease) [5,6] and diabetes [7,8]. Prolonged ER stress could trigger apoptotic cell death through various signal transduction pathways [5,9,10]. Upon chronic ER stress, caspase-12, the ER membrane associated protease belonging to the caspase family, is activated, followed by promoting apoptosis via initiating caspasemediated limited proteolysis cascade [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation